Safeguarding Creditors in the Course of Simplified Reduction of Subscribed Capital - Drnovšek, Gregor (Naše gospodarstvo/Our economy, 2015)
The central characteristics of simplified subscribed capital reduction are its very narrow purpose, and a weakened regime of safeguarding of creditors. The main and, frankly, only purpose of the institution is recovery. It is namely most difficult to expect from a distressed company undergoing simplified subscribed capital reduction, which is first and foremost intended for recovery, to safeguard its creditors in the same extent as in the case of ordinary reduction of subscribed capital. The article provides an analysis of the intent and purpose of simplified subscribed capital reduction and the regulations governing the safeguarding of creditors. Using a descriptive method, subject matter analysis, and comparative legal analysis of the issue, the article elaborates on why regulations governing the safeguarding of creditors are too weak with regard to the effects brought forth by this type of subscribed capital reduction and proposes appropriate supplementation and amendments to applicable legislation.